Cold War redux and the news: Islamic State and the US through each other's eyes. Issue 1 (1st January 2018) - Zelizer, Barbie
ABSTRACT: This article considers the ways in which the media apparatuses of Islamic State and the United States have adopted a Cold War frame for covering each other. In so doing, it demonstrates not only the degree to which U.S. news provides a template for news crafted elsewhere, but also how the past undergirds the present in unknowing and often unpredictable ways.